2016
DOI: 10.1049/mnl.2016.0065
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and antibacterial activity of gold nanoparticles coated with reductase enzymes

Abstract: Potential of luminescent bacteria in production of metal nanoparticles (NPs) has not been well evaluated up until now. These bacteria contain lux operon which is included of reductase enzymes, by increasing bacterial cell density, the expression of aldehyde synthetic enzymes elevate and enhance the yields of NPs synthesis. Therefore, extracellular synthesis of gold NPs (AuNPs) using natural occurring luminescent bacteria, VLA, VLB, VLC and genetically engineered luminescent bacteria, Pseudomonas putida KT2440 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, to the best of our knowledge, there is not any report that indicated the application of luminescent bacteria in TiO 2 NPs production. Beside Au NPs and Se NPs biosynthesis using naturally occurring and genetically engineered luminescent bacteria have been recently achieved in which enzymes stabilized on nanoparticles were recognized as the most predictive agents in nanoparticles biosynthesis [30,31]. In this study, comparison of FTN and HTN characteristics revealed that luciferase enzyme with cofactor FMN as one of the important and most abundant luminescent Vibrio agents are present on nanoparticles surface and bring unique properties.…”
Section: Discussionmentioning
confidence: 83%
“…However, to the best of our knowledge, there is not any report that indicated the application of luminescent bacteria in TiO 2 NPs production. Beside Au NPs and Se NPs biosynthesis using naturally occurring and genetically engineered luminescent bacteria have been recently achieved in which enzymes stabilized on nanoparticles were recognized as the most predictive agents in nanoparticles biosynthesis [30,31]. In this study, comparison of FTN and HTN characteristics revealed that luciferase enzyme with cofactor FMN as one of the important and most abundant luminescent Vibrio agents are present on nanoparticles surface and bring unique properties.…”
Section: Discussionmentioning
confidence: 83%
“…The extracellular approach is the most widely used compared to intracellular synthesis. Various bacterial strains such as Stenotrophomonas maltophilia, Pseudomonas putida, Escherichia coli, and Pseudomonas fluorescence can be used to synthesize the AuNPs [162], [163]. The biosynthesis of AuNPs in these bacteria is associated with an NADPH-dependent reductase enzyme that converts the Au 3+ to Au 0 .…”
Section: Biogenic Synthesis Of Aunps Using Bacteria Strainsmentioning
confidence: 99%
“…Biological methods because of low production costs and almost zero toxic and harmful materials production preferred compared with those of other physicochemical methods [14][15][16][17][18]. Application of different biogenic metal and metalloid NPs such as silver nanostructures (AgNPs) [19], tellurium (Te) nanorods [16], selenium NPs (SeNPs) [20,21], and Fe 3 O 4 -AgCl nanocomposites [22] as novel antimicrobial and anti-biofilm agents have been previously reported.…”
Section: Introductionmentioning
confidence: 99%